Avian Beta Defensin 2 (AvBD2) Gene Polymorphism Identification in IPB-D1 Chicken - Masrurah Masrurah; Isyana Khaerunnisa; Sri Murtini; Cece Sumantri (Jurnal Ilmu Ternak dan Veteriner, 2021)
Avian Beta Defensin 2 (AvBD2) gene, which is located in chromosome 3, plays an important role in the immune system of the chicken by inhibiting the development of microorganisms such as bacteria that infect body tissues. Defensins are produced through epithelial cells immediately after tissue injury or infection, which then processes the maturation of dendritic cells to initiate an immune response in the lymph nodes. The purpose of this study was to discover the polymorphism of the AvBD2 gene in IPB-D1 chickens. PCR and direct-DNA sequencing methods were used to identify the diversity of intron 1, exon 2, and intron 2 AvDB2 genes in 47 chickens. Genotype and allele frequency, and heterozygosity calculations were carried out to obtain information of the AvBD2 gene polymorphism. A total of 10 single nucleotide polymorphisms were found in the AvBD2 gene located in intron 1 (g.4843T>A, g.4853G>A, and g.4859T>C), exon 2 (g.4881A>G, g.4889G>A, and g.5002C>T), and intron 2 (g.5075C>T, g.5111T>G, g.5116G>T, and g.5177G>T). All SNPs are polymorphic. The g.5002C>T mutation causes changes in the amino acid Ala to Val which has the potential to be a candidate for characterizing disease resistance in IPB-D1 chickens.